ASICs and cardiovascular homeostasis - Abboud, François M. (Neuropharmacology, 2015)
In this review we address primarily the role of ASICs in determining sensory signals from arterial baroreceptors, peripheral chemoreceptors, and cardiopulmonary and somatic afferents. Alterations in these sensory signals during acute cardiovascular stresses result in changes in sympathetic and parasympathetic activities that restore cardiovascular homeostasis. In pathological states, however, chronic dysfunctions of these afferents result in serious sympatho-vagal imbalances with significant increases in mortality and morbidity. We identified a role for ASIC2 in the mechano-sensitivity of aortic baroreceptors and of ASIC3 in the pH sensitivity of carotid bodies. In spontaneously hypertensive rats, we reported decreased expression of ASIC2 in nodose ganglia neurons and overexpression of ASIC3 in carotid bodies. This reciprocal expression of ASIC2 and ASIC3 results in reciprocal changes in sensory sensitivity of baro- and chemoreceptors and a consequential synergistic exaggeration sympathetic nerve activity. A similar reciprocal sensory dysautonomia prevails in heart failure and increases the risk of mortality. There is also evidence that ASIC heteromers in skeletal muscle afferents contribute significantly to the exercise pressor reflex. In cardiac muscle afferents of the dorsal root ganglia, they contribute to nociception and to the detrimental sympathetic activation during ischemia. Finally, we report that an inhibitory influence of ASIC2-mediated baroreceptor activity suppresses the sympatho-excitatory reflexes of the chemoreceptors and skeletal muscle afferents, as well as the ASIC1a–mediated excitation of central neurons during fear, threat, or panic. The translational potential of activation of ASIC2 in cardiovascular disease states may be a beneficial sympatho-inhibition and parasympathetic activation.